2008
DOI: 10.1097/01.anes.0000311153.84687.c7
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes Associated with Spinal Anesthesia for Cesarean Delivery in Severe Preeclampsia

Abstract: Spinal anesthesia in severe preeclampsia was associated with clinically insignificant changes in CO. Phenylephrine restored mean arterial pressure but did not increase maternal CO. Oxytocin caused transient marked hypotension, tachycardia, and increases in CO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(67 citation statements)
references
References 26 publications
(30 reference statements)
4
60
0
3
Order By: Relevance
“…Additionally, peripheral vascular resistance decreases moderately throughout gestation, followed by an increase in CO, HR, SV and aortic distensibility, a decrease in peripheral vascular resistance and an increase in left ventricular wall thickness from the second trimester to the end of pregnancy 28. Notably, Dyer et al17 found that CO remained stable throughout cesarean delivery, except for in the period after oxytocin bolus administration (2.5 U). In the present study, however, no significant effects regarding CO or other hemodynamic parameters (except for SVV) were observed after oxytocin administration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, peripheral vascular resistance decreases moderately throughout gestation, followed by an increase in CO, HR, SV and aortic distensibility, a decrease in peripheral vascular resistance and an increase in left ventricular wall thickness from the second trimester to the end of pregnancy 28. Notably, Dyer et al17 found that CO remained stable throughout cesarean delivery, except for in the period after oxytocin bolus administration (2.5 U). In the present study, however, no significant effects regarding CO or other hemodynamic parameters (except for SVV) were observed after oxytocin administration.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy patients, the maximum change in CO has been shown to correlate better to uteroplacental blood flow than to upper arm blood pressure 24. More recently, Dyer et al17 tested the hypothesis that continuous monitoring of CO in patients with severe preeclampsia during spinal anesthesia for cesarean delivery would give better information on the uteroplacental blood flow than determination of the mean radial artery blood pressure. It was found that CO, as inferred from pulse-wave analysis, did not decrease significantly from baseline if the mean radial artery blood pressure was maintained at baseline levels with intermittent vasopressors; therefore, it was concluded that spinal anesthesia was associated with clinically insignificant changes in CO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations